On Trend : The Business of Forecasting the Future - Powers, Devon (Book collections on Project MUSE., 2019)
Trends have become a commodity--an element of culture in their own right and the very currency of our cultural life. Consumer culture relies on a new class of professionals who explain trends, predict trends, and in profound ways even manufacture trends. On Trend delves into one of the most powerful forces in global consumer culture. From forecasting to cool hunting to design thinking, the work done by trend professionals influences how we live, work, play, shop, and learn. Devon Powers' provocative insights open up how the business of the future kindles exciting opportunity even as its practices raise questions about an economy increasingly built on nonstop disruption and innovation. Merging industry history with vivid portraits of today's trend visionaries, Powers reveals how trends took over, what it means for cultural change, and the price all of us pay to see--and live--the future.